Pengaruh Video Wisata Daerah terhadap Kemampuan Menulis Teks Drama Siswa Kelas XI RPL SMK Multi Mekanik Masmur - Panggabean, Ennida Sari; Elmustian, Elmustian; Zulhafizh, Zulhafizh (LPPM Institut Pendidikan Nusantara Global, 2025)
This research aims to determine students' ability to write drama texts before and after using regional tourism videos, as well as to analyze the effect of using tourist videos on the learning outcomes of class XI students at SMK Multi Mekanik Masmur. This research is expected to provide insight into the effectiveness of using video as a learning medium in improving students' drama writing skills. This type of research is quantitative research with a pre-experimental method using a pretest-posttest design. The research sample consisted of 30 students selected by purposive sampling from a population of 195 students. Data was obtained through writing tests, questionnaires and observations, then analyzed using descriptive and inferential statistical tests. The research results show that students' ability to write drama texts before using regional tourism videos has an average pretest score of 63.89, which indicates that there is a level of understanding that needs to be improved. After using regional tourism videos in the form of the Siak Palace and the Sang Nila Museum, the average posttest score increased to 86.57, which reflects significant progress in students' ability to write drama texts. Hypothesis testing shows that the t-count of 16.9 is higher than the t-table of 1.70, with a significance threshold of 0.05 and degrees of freedom (df) of 29. This indicates that students' writing skills before and after receiving regional tourism video treatment are significantly different.